2021
DOI: 10.1186/s12889-021-11335-1
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to HIV pre-exposure prophylaxis (PrEP) uptake through a community-based intervention strategy among adolescent girls and young women in Seme Sub-County, Kisumu, Kenya

Abstract: Background While the introduction of HIV Pre-Exposure Prophylaxis (PrEP) as an HIV prevention strategy has allowed women to exercise more control over the reduction of HIV transmission rates, adolescent girls and young women in Sub-Saharan Africa continue to experience higher rates of HIV infections and bear the greatest disease burden. Understanding progress in PrEP uptake among adolescent girls and young women would enhance risk reduction in this vulnerable population. The Determined, Resilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
88
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(119 citation statements)
references
References 26 publications
(38 reference statements)
4
88
0
Order By: Relevance
“…In fact, a review of early lessons from PrEP demonstration projects in SSA found PrEP initiation and impact amongst AGYW to be greater in projects that integrated PrEP into youth-friendly clinics that combined a range of different sexual and reproductive health services [ 10 ]. Recognising their lack of financial resources and trained staff to provide timely and responsive care to AGYW, challenges also identified by healthcare providers in Kenya [ 11 ], all the healthcare providers in our study recommended further investments in the healthcare cadre involved in PrEP provision.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, a review of early lessons from PrEP demonstration projects in SSA found PrEP initiation and impact amongst AGYW to be greater in projects that integrated PrEP into youth-friendly clinics that combined a range of different sexual and reproductive health services [ 10 ]. Recognising their lack of financial resources and trained staff to provide timely and responsive care to AGYW, challenges also identified by healthcare providers in Kenya [ 11 ], all the healthcare providers in our study recommended further investments in the healthcare cadre involved in PrEP provision.…”
Section: Discussionmentioning
confidence: 99%
“…They also found side-effects to be an issue; albeit an issue AGYW learnt to overcome. A focus group study with AGYW in Kenya, however, found side-effects to constitute a barrier to PrEP uptake and engagement [ 11 ]. The study also noted issues related to the packaging of PrEP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A separate study identified barriers and facilitators affecting the PrEP care continuum in Kenya among girls and young women by conducting key informant interviews with staff, providers, and medical leaders; results highlight the importance of using a safe space model, peer mentors, including parents and partners in PrEP education, and active stakeholder involvement. 19…”
Section: Introductionmentioning
confidence: 99%